Matrix effects reshape organic aerosol volatility and atmospheric persistence - Qiaorong Xie; Abigail M. Smith; Sara C. Botero-Carrizosa; Steven A. L. Sharpe; Gali Dekel; Nicole A. June; Manish Shrivastava; Yuqing Dai; Kevin Ridgway; Christian L’Orange; Shantanu H. Jathar; Katherine S. Hopstock; et al. (Proceedings of the National Academy of Sciences, 2026)
The volatility of individual species is a fundamental property governing the gas-particle partitioning of organic aerosols. However, in complex organic mixtures, a compound’s apparent volatility may differ from its intrinsic volatility, depending on the matrix’s chemical composition. Herein, we systematically investigate component-resolved, mixture-specific volatility for more than 1,500 individual species across 33 proxies and chemically complex mixtures representative of selected organic aerosol types. The results show that species in simplified proxies and reference mixtures with limited components follow a higher-volatility trend that approaches their intrinsic values, whereas species present in ambient and biomass-burning organic aerosols exhibit the opposite behavior, with systematically reduced apparent volatility attributable to matrix effects. Using levoglucosan (LG), a representative biomass-burning tracer, as an illustrative example, we find that its volatility in complex organic mixtures is reduced by 1 to 4 orders of magnitude relative to its intrinsic volatility in pure LG. This pronounced reduction underscores strong matrix effects that substantially suppress the apparent volatility of individual species in mixed systems. Machine-learning analysis further indicates that mixture-dependent molecular metrics are more predictive of apparent volatility than compound-specific molecular properties that define intrinsic volatility. Collectively, these findings highlight the critical role of intermolecular interactions in governing gas-particle partitioning in multicomponent systems. This study provides strong evidence that matrix effects significantly influence the apparent volatility of individual species in aerosols and other environmental organic mixtures and should be explicitly considered in volatility prediction frameworks and aerosol transport models.